Making American Culture - Bradley, P. author. aut Link
XII, 240 p. 11 illus.
Keywords: This book offers a social and cultural history of American culture in the formative years of the twentieth century, examining forms such as vaudeville, early film, popular songs, modernist art, and many others in the context of contemporary social changes.